Molecular identification of sex in diodecious canarium odontophyllum miq - Tan, Hsiao Tien (Universiti Malaysia Sarawak, UNIMAS, 2006)
Canarium odontophyllum or locally known as dabai is currently acknowledged by the Department of Agriculture, Sarawak as a wild fruit species that has immediate potential for commercial exploitation. Apart from the effort in improving the vegetative propagation technique, it is considered an advantage to develop a technique to distinguish the sex-type at the seedling stage. Direct Amplification of Minisatellite-region DNA (DAMD) analysis was used to detect fragments of DNA that are tightly linked to the sex of C. odontophyllum. The PCR-derived fragments of DNA were generated using M13 universal primer. Two diagnostic bands were successfully identified based on the M13 DNA profiles generated, i.e. locus M13-10 from male C. odontophyllum and locus M13-11 from female C. odontophyllum. The two diagnostic bands identified were then used to infer the sex of ten C. odontophyllum seedlings. The preliminary result suggested that seedlings samples 1, 4, 6, 7, 8 and 9 were male; samples 3a and 3b were female whereas sex of samples 2 and 5 were unknown.